T Follicular Helper Cells As a New Target for Immunosuppressive Therapies - Yan, Lin; de Leur, Kitty; Hendriks, Rudi W.; van der Laan, Luc J. W.; Shi, Yunying; Wang, Lanlan; Baan, Carla C. (Frontiers in Immunology, 2017)
Over the past decade antibody-mediated (humoral) rejection has been recognized as a common cause of graft dysfunction after organ transplantation and an important determinant for graft loss. In humoral alloimmunity, T follicular helper (Tfh) cells play a crucial role, because they help naïve B cells to differentiate into memory B cells and alloantibody-producing plasma cells within germinal centers. In this way, they contribute to the induction of donor-specific antibodies, which are responsible for the humoral immune response to the allograft. In this article we provide an overview of the current knowledge on the effects of immunosuppressive therapies on Tfh cell development and function, and discuss possible new approaches to influence the activity of Tfh cells. In addition, we discuss the potential use of Tfh cells as a pharmacodynamic biomarker to improve alloimmune risk stratification and tailoring of immunosuppression in order to individualize therapy after transplantation.